Role of carrier material in encapsulation of yeast (Saccharomyces cerevisiae) by spray drying. Issue 8 (11th June 2017) - Chandralekha, A.; Rani, Anupama; Tavanandi, Hrishikesh A.; Amrutha, N.; Hebbar, Umesh; Raghavarao, K. S. M. S.
ABSTRACT: Yeast was encapsulated using different carrier materials and their combinations to explore the possible synergistic effect of carrier material during encapsulation using spray drying. Freeze-drying was performed for comparison. The dried cell powders were analyzed for the quality aspects (morphology, flowability, and storage stability). The best results were observed, with a combination of whey protein and corn starch (cell survival: 82.37% and yield: 56%, w/w) with a shelf life of 6 months (with only 10% reduction in cell survival). The survival was found to be 40% without any carrier material, which decreased to less than 25% within 4 weeks.